Solidarity in Urban Divide: Sociological Study Community BTN. Citra Persada Nyamarai, Labuapi West Lombok - Sumitro, Sumitro; Rakhmat Nur Adhi; Mila Noviana; Tauhid Hidayat (Socio-Economic and Humanistic Aspects for Township and Industry, 2025)
This study examines the forms and dynamics of social solidarity among urban communities living in the BTN Citra Persada Nyamarai housing complex, West Lombok. This area reflects the social reality of urban communities living in physical and social barriers due to the design of residential spaces, high mobility, and diverse socio-economic backgrounds. A qualitative approach was used in this study with data collection techniques through participatory observation, in-depth interviews, and documentation. The findings show that although interactions between residents tend to be limited and fragmented, there are patterns of solidarity that develop through informal mechanisms such as social gatherings, religious activities, and environmental emergency response. This study reveals that solidarity in urban spaces does not always weaken, but undergoes a transformation in form from mechanical solidarity to organic solidarity based on shared needs and interests. The results of this study contribute to the understanding of how urban communities build social cohesion in the context of changes in spatial planning and modern lifestyles.